The Impact of Performance Based Budget (Pbb) on Projects Effectiveness, Quality and Sustainability in Fako and Meme Divisions of the South West Region, Cameroon - Anyingang , Roland A. (Archives of Business Research, 2021)
The study examined the impact of performance based budget on projects effectiveness, quality and sustainability in Fako and Meme Divisions of the South West Region, Cameroon. Three specific objectives were formulated to guide this study. The objectives investigated the impact of performance based budget on the effectiveness of projects, the impact of performance based budget on the quality of projects and the impact of performance based budget on the sustainability of projects. Ex-post facto research design was used for this study. The sample of this study was made up 420 respondents comprising of service providers, beneficiaries of the projects and staff of the Regional Delegation of Water and Energy and the Regional Delegation of Public Works in Fako and Meme Divisions. A well validated structured questionnaire was used for data collection. Data collected were analyzed using descriptive statistics and dependent t-test. Findings revealed that there exist a significant difference in the quality of roads, water and electricity projects before and after implementation of performance based budget with the quality of roads higher after the full implementation than before the implementation of PBB. There exist a significant difference in the effectiveness of road, water and electricity projects before and after implementation of water projects, and there exist a significant difference in the sustainability of road, water and electricity projects before and after implementation of performance based budget. The study recommended that the effectiveness of the budgetary system should be improved so that the quality and sustainability of projects will be obtained. Moreover, good budget begets good results.